ANALISIS PENGARUH KENAIKAN UPAH MINIMUM PROVINSI, IPM, DAN PDRB TERHADAP TINGKAT KESEMPATAN KERJA DI PROVINSI DKI JAKARTA TAHUN 2011-2021 - Nida Ulhafiah; Fitrie Arianti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2023)
This study discusses job opportunities in six administrative districts/cities of DKI Jakarta Province which are influenced by several factors such as wage levels, quality of human resources, and regional economic growth. The purpose of this study is to analyze how the Provincial Minimum Wage (UMP), Human Development Index (IPM), and Gross Regional Domestic Product (GRDP) as independent variables affect the level of employment during the 2011-2021 period. This study uses secondary data obtained from the Central Bureau of Statistics (BPS). This data is then processed using panel data regression with the Common Effect Model (CEM) method.The results showed that partially the Provincial Minimum Wage (UMP) had a negative and insignificant effect on the level of employment opportunities, the Human Development Index (IPM) had a positive and significant effect on the level of employment opportunities, and GRDP had a negative and significant effect on the level of employment opportunities. However, simultaneously the three variables have a significant effect on the level of employment opportunities in regencies/cities in DKI Jakarta Province. The magnitude of the influence of the UMP, HDI, and GRDP in explaining the effect on the level of employment opportunity is 34.18%, while the remaining 65.82% is influenced by other factors outside the model.